2020
DOI: 10.5041/rmmj.10386
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis in Children

Abstract: Conflict of interest: Adi Aran reports receiving personal fees and stock options for advisory roles at BOL Pharma. No potential conflict of interest relevant to this article was reported for Dalit Cayam-Rand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 117 publications
0
41
0
16
Order By: Relevance
“…Progress in the patients’ autonomy, increased motor, and cognitive performances as well as communication and social interaction improvements were also reported. The expected anticonvulsant effect of CBD ( Mullard, 2018 ; Silvestro et al, 2019 ; Alves et al, 2020 ; Aran and Cayam-Rand, 2020 ; Lazarini-Lopes et al, 2020 ) was confirmed in two studies in which seizures were at least partially or even completely controlled ( Bar-Lev Schleider et al, 2019 ; Fleury-Teixeira et al, 2019 ). In accordance with these studies, a recent case report about a 15-year-old boy with ASD who was treated with CBD-enriched cannabis extract oil (CBD/THC ratio of 20:1; 4 mg CBD and 0.2 mg THC twice a day) reported that CBD-based treatment aided in the control of ASD-related behavioral symptoms, core social communication abilities, anxiety, sleep difficulties, and body weight ( Ponton et al, 2020 ).…”
Section: Reviewed Studies On Autism Spectrum Disordermentioning
confidence: 81%
“…Progress in the patients’ autonomy, increased motor, and cognitive performances as well as communication and social interaction improvements were also reported. The expected anticonvulsant effect of CBD ( Mullard, 2018 ; Silvestro et al, 2019 ; Alves et al, 2020 ; Aran and Cayam-Rand, 2020 ; Lazarini-Lopes et al, 2020 ) was confirmed in two studies in which seizures were at least partially or even completely controlled ( Bar-Lev Schleider et al, 2019 ; Fleury-Teixeira et al, 2019 ). In accordance with these studies, a recent case report about a 15-year-old boy with ASD who was treated with CBD-enriched cannabis extract oil (CBD/THC ratio of 20:1; 4 mg CBD and 0.2 mg THC twice a day) reported that CBD-based treatment aided in the control of ASD-related behavioral symptoms, core social communication abilities, anxiety, sleep difficulties, and body weight ( Ponton et al, 2020 ).…”
Section: Reviewed Studies On Autism Spectrum Disordermentioning
confidence: 81%
“…Research suggests that CBD may also interact with benzodiazepines. It has been noted that the active metabolites of benzodiazepines increase significantly with concurrent use of CBD and CBD-rich medical marijuana [26].…”
Section: Drug Interactionsmentioning
confidence: 99%
“…Of those 19, ten articles were literature reviews regarding the treatment of autism with cannabis derived products. [2][3][4][5][6][7][8][9][10][11] The remaining nine articles consisted of a viewpoint, ethics statement, letter, two studies done on adult populations, and four studies done using cannabis-based products for the treatment of autism related symptoms in children. [12][13][14][15][16][17][18][19][20] The 2019 Schleider et al article was about a prospective study looking at the safety and efficacy of medical cannabis treatment in children with ASD.…”
Section: Related Literaturementioning
confidence: 99%